SPATIAL DYNAMICS OF PELAGIC FISH AGGREGATION IN THE JAVA SEA BASED ON HYDRO-ACOUSTICS - Bambang Sadhotomo (Indonesian Fisheries Research Journal, 2001)
This study was based on a concept called acoustic population estimation. This is defined as a population of echoes which is based on the hyphothesis that a synthesis of biological and behavioural characteristics of the species (within a community) characterizes the community (Gerlotto & Marchal, 1987).